2021
DOI: 10.1111/jcmm.16683
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharide attenuates LPS‐related inflammatory osteolysis by suppressing osteoclastogenesis by reducing the MAPK signalling pathway

Abstract: Skeletal metabolic homeostasis integrity is sustained and orchestrated by osteoclast interceded bone resorption and osteoblast interceded bone formation. 1 An increase in osteoclast formation contributes to excessive bone remodelling and thus induces many osteolytic problems, including osteoporosis, 2 aseptic loosening of prostheses, 3 inflammatory osteolysis, 4 rheumatoid arthritis 5 and metastatic cancers. 6 Among them, inflammatory osteolysis, characterized by excessive bone mass loss, is mainly attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Subsequently, APS with different concentrations was adopted to treat AR guinea pigs, after which the sneezing and rubbing times of AR guinea pigs were reduced, and the levels of OVA-sIgE, OVA-sIgG1, and pro-inflammatory cytokines were declined in a dose-dependent manner. Relevant studies demonstrated that APS could effectively alleviate inflammatory responses induced by lipopolysaccharide in inflammatory osteolysis 35 and intestinal inflammatory damages in goslings, 36 further supporting that APS imparted an ameliorating role to inflammatory responses in AR guinea pigs.…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, APS with different concentrations was adopted to treat AR guinea pigs, after which the sneezing and rubbing times of AR guinea pigs were reduced, and the levels of OVA-sIgE, OVA-sIgG1, and pro-inflammatory cytokines were declined in a dose-dependent manner. Relevant studies demonstrated that APS could effectively alleviate inflammatory responses induced by lipopolysaccharide in inflammatory osteolysis 35 and intestinal inflammatory damages in goslings, 36 further supporting that APS imparted an ameliorating role to inflammatory responses in AR guinea pigs.…”
Section: Discussionmentioning
confidence: 89%
“…Known as a highly conserved important constituent almost of all Gram-negative bacteria, Lipopolysaccharide (LPS) can promote the release of inflammatory factors such as TNF-a and IL-1b, increase the secretion of RANKL, and enhance osteoclast formation and osteolysis ( Islam et al, 2007 ; Guo et al, 2014 ). Thus, LPS is extensively used in the investigation of inflammatory osteolysis ( Islam et al, 2007 ; Yang et al, 2019 ; Yang et al, 2021 ). In our study, LPS was injected on the surfaces of mice’s calvarias to create inflammatory bone erosion models.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bone diseases, usually caused by some infectious bone diseases, such as purulent spondylitis, purulent osteomyelitis, and periprosthetic infection, induce abnormal activation and overproliferation of osteoclasts and eventually lead to osteolysis and bone mass loss ( Kim et al, 2013 ). Current studies have found that the release of endogenous products of bacteria can activate immune cells, cause excessive proliferation of osteoclasts and enhance bone resorption ( Mbalaviele et al, 2017 ; Yang et al, 2021 ). Over the past few decades, there have been some advances in the treatment of inflammatory osteolytic bone diseases, but some limitations remain.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results suggested that CaSR promoted the expression of NF-κB p65 and PTHrP, which is closely related to bone metastasis of lung adenocarcinoma [12]. Several studies have shown that APS inhibits the activation of MAPK and ROS signaling pathways during OCs diferentiation associated with RANKL induction, and APS inhibits the production of infammatory factors and chemokines by inhibiting activation of the MAPK and NF-κB infammatory pathways [41]. In this study, we found that APS not only inhibited the expression of CaSR in lung adenocarcinoma A549 cells but also inhibited the expression of PTHrP and NF-κB p65 induced by CaSR overexpression.…”
Section: Casrmentioning
confidence: 95%
“…It has been shown that APS improves the balance between OCs and OBs [15]. APS acts as an inhibitor to reduce the activation of MAPK and ROS signaling pathways during OCs genesis associated with RANKL induction, thus suppressing OCs formation due to LPS stimulation [41]. It has also been shown that strontiumbased APS promotes OBs diferentiation and promotes the proliferation of OBs via the TLR4 signaling pathway, then ossifcation occurs [42,43].…”
Section: Aps (100 Mgmentioning
confidence: 99%